Konsep Keadilan dalam Hukum Islam: Kajian Normatif dan Aplikatif - Kamalin, Muhammad; Winario, Mohd; Rafiqoh, Lailan (Journal of Legal Sustainability, 2025)
This study aims to comprehensively analyze the concept of justice in Islamic law from both normative and applicative perspectives, by examining how these justice values are implemented in contemporary legal practices. From the normative perspective, this research explores the primary sources of Islamic teachings such as the Qur’an, Hadith, ijma’, qiyas, as well as the views of classical and modern scholars, which explain the fundamental principle of justice as an integral part of maqashid al-shariah. Meanwhile, from the applicative perspective, this study examines the implementation of justice principles within the Sharia judicial system in several countries, both those that adopt Islamic law as the main legal foundation and those that integrate it partially into their national legal systems. The research method employed is library research with a normative qualitative approach that combines content analysis and comparative study of various literature and legal documents. The findings indicate that justice in Islamic law is not only understood as the imposition of proportional punishment (retributive), but also includes efforts toward restoration (restorative) and prevention (preventive) in order to uphold public interest, protect individual rights, and achieve social balance. However, the application of the concept of justice in modern contexts still faces challenges, particularly in terms of legal interpretation and the process of harmonizing Islamic law with positive legal systems in various Muslim-majority countries.